Crystallization Modulation and Holistic Passivation Enables Efficient Two-Terminal Perovskite/CuIn(Ga)Se2 Tandem Solar Cells - Cong Geng; Kuanxiang Zhang; Changhua Wang; Chung Hsien Wu; Jiwen Jiang; Fei Long; Liyuan Han; Qifeng Han; Yi-Bing Cheng; Yong Peng (Nano-Micro Letters)
Highlights Integrating perovskite solar cells onto irregular rough CuIn(Ga)Se2 (CIGS) surfaces remains a challenge; new strategy was explored to develop monolithic perovskite/CIGS tandem solar cell by manipulating the crystallization of perovskite. Surface reconstruction and field-effect passivation are developed synergistically to issue complex interface relationship between perovskite and C60. The champion  power conversion efficiency （PCE） of 24.6% realized, providing significant commercial opportunities for all thin-film-based perovskite/CIGS tandem cells.